Identifikasi wilayah Syam berdasarkan Mu’jam al-Buldān oleh al-Ḥamawī: kajian terhadap huruf al-Shīn - Thuraya Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Syam is a name of a place that is often mentioned in classical Arabic texts, including hadith texts. However, contemporary literature reveals an inaccurate description of the area that includes the territory of Syam in the past. Hence, this study aims to identify the territory of Syam by focusing on the al-Shīn chapter in the book Mu'jam al-Buldān by Yāqūt al-Ḥamawī. Data collection involved library research with Mu'jam al-Buldān being the primary source and other related secondary sources for further explanation. The study began by focusing on the names of locations classified by al-Ḥamawī in the al-Shīn chapter that was part of the territory of Sham. This was followed by compiling geographic information of each location. Then, the textual analysis approach was used to process the data. Subsequently, this study identified 30 names of places that were part of the territory of Syam, which includes countries known today as Saudi Arabia, Israel, Iraq, Jordan, Lebanon, Egypt, Palestine, Syria, and Turkey. In this regard, this study is of the view that it is appropriate to identify the geographical aspects of Syria, especially if the study is related to that area. Therefore, any confusion or misunderstanding about the territory of Syam can be avoided and rectified.